As Clinical Markers, Hand-Foot-Skin Reaction and Diarrhea Can Predict Better Outcomes for Hepatocellular Carcinoma Patients Receiving Transarterial Chemoembolization plus Sorafenib - Lei Liu; Enxin Wang; Lin Li; Dongyu Chen; Kun Peng; Mengmeng Wang; Guohong Han (Canadian Journal of Gastroenterology and Hepatology)
Background. Combination therapy of transarterial chemoembolization plus sorafenib (TACE-S) has been proven to be safe and effective for hepatocellular carcinoma (HCC); however, this combination therapy is associated with a high incidence of adverse events (AEs). Our study focused on the relationships between AEs and treatment outcomes and aimed to discover AE-based clinical markers that can predict the survival benefits of combination treatment. Methods. From January 2010 to June 2014, a total of 235 HCC patients treated with TACE-S were retrospectively enrolled. Major sorafenib-related AEs were prospectively recorded, and their correlations with overall survival (OS) were analysed using time-dependent covariate Cox regression analyses. Results. The majority of the patients (200, 85.1%) were male, and the median age was 51 years old. After two years of follow-up, the median OS of the study population reached 12.4 months. In all, 218 patients (92.8%) presented at least one AE, and 174 (74.0%) suffered AEs ≥2 grade. Based on time-dependent multivariate analyses, the development of hand-foot skin reaction (HFSR) ≥2 grade (HR = 0.43, 95% CI: 0.32–0.58, P<0.001) and diarrhoea ≥1 grade (HR = 0.72, 95% CI: 0.53–0.97, P=0.029) were identified as independent predictors of prolonged OS. Moreover, patients who developed both HFSR ≥2 grade and diarrhoea ≥1 grade achieved better outcomes than those patients who developed either or neither of these AEs (HR = 1.51, 95% CI: 1.11–2.06, P=0.009). Conclusions. The development of HFSR ≥2 grade or diarrhoea ≥1 grade during TACE-S treatment indicated prolonged OS, and these AEs should be considered important clinical markers for predicting patient prognoses.